Dynamic analysis of a piezoelectric system to compensate for workpiece deformations in flexible milling. (July 2017) - Diez, E.; Leal-Muñoz, E.; Perez, H.; Vizan, A.
Highlights: Comprehensive dynamic modelling of the flexible milling process. Novel in-process strategy for error compensation in milling of flexible components. Modelling of the flexible milling system dynamics with deformation compensation. Simulation of the flexible milling system dynamic performance with compensation. Implementation of the in-process compensation system in a machine tool. Abstract: This paper presents a system to compensate for workpiece deformations in flexible peripheral milling based on piezoelectric actuators, and its dynamic model. The compensation system is formed by a flexure hinge based worktable, which is moved by a piezoelectric actuator to compensate the workpiece deformation induced by cutting forces. The command signal to the actuator is calculated from measured cutting forces. When the compensation system is acting, the cutting force values from the flexible system reach the corresponding values for the rigid model, ensuring that the tool is cutting the nominal width of cut. The model considers the performance of three subsystems which interact between them during the machining process: the positioning system, the structural assembly and the flexible machining process itself. The parameter identification of the dynamic model was experimentally obtained from modal analysis and a system identification procedure. The cutting forces in the model take into account the workpiece deformation and its compensation on the instantaneous chip thickness and the width of cut. The proposed compensation system has its main application in the machining of small parts of thin walls although the methodology is applicable to larger parts.